5x+11=49

Simple and best practice solution for 5x+11=49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+11=49 equation:


Simplifying
5x + 11 = 49

Reorder the terms:
11 + 5x = 49

Solving
11 + 5x = 49

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + 5x = 49 + -11

Combine like terms: 11 + -11 = 0
0 + 5x = 49 + -11
5x = 49 + -11

Combine like terms: 49 + -11 = 38
5x = 38

Divide each side by '5'.
x = 7.6

Simplifying
x = 7.6

See similar equations:

| -15+5(-2)=-5y | | 3x(3x+2)=3x-4 | | -15+5(0)=-5y | | 9x+25=43 | | -15+5(2)=-5y | | -2(2x-6)=32 | | 6x^2=x-24 | | 7x-10+x+4=90 | | -4=(-2) | | -4=(0) | | 7x-10+x+4=180 | | 24x-3y-18=0 | | -2=(2) | | 2pq+pq= | | 6*(x+2)= | | (-14)+3= | | 2+3y=19 | | -4=2 | | 4+x=-10 | | 4x+21+11x+9=180 | | 9g-13=2g | | 7-15=-(3-8) | | 3n+7=4 | | 7x-10=x+4 | | y+2=-3(-2)+8 | | c+6=-3 | | y+2=-3(0)+8 | | -3.1+x=-2.1 | | 6a-3=2 | | y+2=-3(2)+8 | | -3x(2x-3)=-5x+5 | | 6n+3=-2n+12 |

Equations solver categories